Assessment of programmed cell death 1 and its programmed cell death ligand 1 levels in vitiligo - Hanan R. Nada; Ahmed Mourad; Laila A. Rashed; Ghada M. El-Hanafy; Nermeen M.A. Abdallah; Mohamed M. Abdelhady (Journal of the Egyptian Women’s Dermatologic Society)
Background Programmed cell death 1 (PD-1) is a cell surface protein that serves as an immune checkpoint in conjunction with its two ligands, PD-L1 and PD-L2. Recently, there has been a lot of interest in the role of the PD-1/PD-L1 pathway in immunoregulation. Objective To assess both PD-1 and PD-L1 levels in vitiligo patients’ marginal and nonlesional biopsies compared with normal controls and to correlate them with disease parameters. Patients and methods A total of 30 vitiliginous patients and 30 age and sex-matched controls were included. Full history and clinical examination were done and ELISA measured tissue levels of PD-1 and PD-L1 from lesional and nonlesional biopsies. Results Levels of tissue PD-1 in marginal biopsies (mean 7.89±2.48 ng/mg) were significantly higher than in nonlesional biopsies (mean 3.65±1.11 ng/mg; P<0.001) and significantly higher than the control PD-l level (mean 1.47±0.499 ng/mg; P<0.001). Nonlesional PD-1 level was also significantly higher than the control PD-l level (P<0.001). A statistically significant positive correlation was found between marginal and nonlesional PD-1 levels; (rho=0.792, P<0.001). Levels of tissue PD-L1 in marginal biopsies (mean 115±7.86 pg/mg) were significantly lower than in nonlesional skin (mean 194±8.12 pg/mg; P<0.001), and significantly lower than in controls (mean 283±27.8 pg/mg; P<0.001). Nonlesional PD-L1 level was also significantly lower than the control PD-Ll level (P<0.001). Conclusion Our results suggest that the PD-1/PD-L1 checkpoint seems to be implicated in the loss of peripheral tolerance in human vitiligo, with PD-1 being highly expressed, yet insufficiently stimulated due to lack of local PD-L1 expression. Since PD1 plays an important role, its agonists may have therapeutic implications in vitiligo and other autoimmune diseases but need wider-scale studies before clinical implementation.